1991
DOI: 10.1073/pnas.88.23.10961
|View full text |Cite
|
Sign up to set email alerts
|

M-15: high-affinity chimeric peptide that blocks the neuronal actions of galanin in the hippocampus, locus coeruleus, and spinal cord.

Abstract: The 20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
72
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(77 citation statements)
references
References 22 publications
3
72
2
Order By: Relevance
“…As shown in Table I, both GALR1 and GALR2 receptors bound the full-length peptide porcine galanin-(1-29) with high affinity, as well as the truncated analogs galanin-(1-16) and galanin-(1-15). Both receptor subtypes also displayed high affinity for the putative galanin antagonists M15, M35, M40, and C7 (15,29,34,35), all of which share a common galanin-(1-13) N terminus. Furthermore, binding affinity was lost for either receptor subtype when the first two N-terminal residues were deleted, as in the case of galanin- .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table I, both GALR1 and GALR2 receptors bound the full-length peptide porcine galanin-(1-29) with high affinity, as well as the truncated analogs galanin-(1-16) and galanin-(1-15). Both receptor subtypes also displayed high affinity for the putative galanin antagonists M15, M35, M40, and C7 (15,29,34,35), all of which share a common galanin-(1-13) N terminus. Furthermore, binding affinity was lost for either receptor subtype when the first two N-terminal residues were deleted, as in the case of galanin- .…”
Section: Resultsmentioning
confidence: 99%
“…Multiple receptor subtypes are proposed to underlie the physiological effects of galanin (15)(16)(17)(18), but until recently only one cloned galanin receptor subtype (GALR1) had been described (19 -21). We report here the isolation by expression cloning and the pharmacological characterization of a novel galanin receptor from a rat hypothalamic cDNA library.…”
mentioning
confidence: 99%
“…In contrast to these inhibitory actions, exogenous galanin has no effect on the increased release of ACh that occurs when a rodent is exposed to a novel environment (9). Neither of the galanin antagonists has an effect on ACh release or on cognition in the absence of exogenously administered galanin (5,6). Similarly, whereas exogenous galanin inhibits long-term potentiation (LTP) in hippocampal CA1 slices that is reversed by the M40 galanin antagonist, M40 has no effect on LTP when applied alone (10).…”
mentioning
confidence: 99%
“…These findings have led to a number of functional studies addressing the role played by galanin in the basal forebrain cholinergic system, including its effects on acetylcholine (ACh) release as well as learning and memory. Acute administration of galanin into the hippocampus or third ventricle of rodents inhibits scopolamineinduced ACh release in a dose-dependent manner and is reversed by the coadministration of the chimeric-peptide galanin receptor antagonists M15 and M40 (5,6). Centrally administered galanin also has inhibitory effects on several tests of learning and memory (7,8).…”
mentioning
confidence: 99%
“…Galanin hyperpolarizes noradrenergic cell bodies in the locus coeruleus (11) and inhibits the release of glutamate, but not of raminobutyric acid, in the hippocampus (12). This fragmentary list of the effects of exogenously applied galanin explains much of the interest in this neuropeptide in psychopharmacology, in endocrinology, in prevention of anoxic damage (13), and in management of chronic pain and explains the interest in galanin antagonists as possible therapeutic agents in Alzheimer disease (14,15 (17) and by receptor autoradiography (18,19) in the central nervous system (CNS) and in the periphery. It was shown that actions mediated by galanin receptors involve pertussis toxin-ADP-ribosylable G proteins of inhibitory (Gi) or regulatory (Go) type (20)(21)(22).…”
mentioning
confidence: 99%